Pengaruh Kepemimpinan dan Disiplin Kerja Terhadap Kinerja Pegawai Melalui Motivasi Kerja: Survey pada Rumah Sakit Umum Daerah Kabupaten Bolaang Mongondow Selatan - Rizal, Abdul; Rahmisyari; Arifin (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This study aims to analyze the influence of leadership and work discipline on employee performance through work motivation at the Regional General Hospital of South Bolaang Mongondow Regency. The study used a quantitative approach with a survey method. Data analysis uses SemPLS analysis using SmartPLS software version 3.0. Data collection from a number of respondents who work at the South Bolaang Mongondow Regional General Hospital through a structured questionnaire. The results of the analysis show that leadership has no significant effect on employee motivation, but leadership has a significant effect on employee performance. Work discipline is proven to have a significant influence on work motivation and employee performance. In addition, work motivation has a significant influence on employee performance. Another important finding is that employee motivation does not mediate the relationship between leadership and employee performance, but acts as a mediator in the relationship between work discipline and employee performance. This study makes theoretical and practical contributions by highlighting the importance of work discipline in improving motivation and performance, and showing that effective leadership can directly affect employee performance without going through motivation.